2010
DOI: 10.1128/jvi.01347-09
|View full text |Cite
|
Sign up to set email alerts
|

The Single-Stranded DNA Genome of Novel Archaeal Virus Halorubrum Pleomorphic Virus 1 Is Enclosed in the Envelope Decorated with Glycoprotein Spikes

Abstract: Only a few archaeal viruses have been subjected to detailed structural analyses. Major obstacles have been the extreme conditions such as high salinity or temperature needed for the propagation of these viruses. In addition, unusual morphotypes of many archaeal viruses have made it difficult to obtain further information on virion architectures. We used controlled virion dissociation to reveal the structural organization of Halorubrum pleomorphic virus 1 (HRPV-1) infecting an extremely halophilic archaeal host… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
88
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 59 publications
(93 citation statements)
references
References 53 publications
5
88
0
Order By: Relevance
“…The same is true for SH1, where glycolipids, which constitute approximately 20 % of the total host lipids, failed to be detected in viral lipid extracts [7]. Selective incorporation of lipids has been shown for other non-tailed, membrane-containing icosahedral viruses [8,9,30,31], whereas the lipid composition of archaeal and bacterial pleomorphic viruses reflects the host lipid composition [4,41]. Three of the 10 identified structural proteins of P23-77 have been shown to be associated with the capsid, and five with the membrane, while the remaining two could not be unambiguously located [21].…”
Section: The New Genus Gammasphaerolipovirusmentioning
confidence: 79%
“…The same is true for SH1, where glycolipids, which constitute approximately 20 % of the total host lipids, failed to be detected in viral lipid extracts [7]. Selective incorporation of lipids has been shown for other non-tailed, membrane-containing icosahedral viruses [8,9,30,31], whereas the lipid composition of archaeal and bacterial pleomorphic viruses reflects the host lipid composition [4,41]. Three of the 10 identified structural proteins of P23-77 have been shown to be associated with the capsid, and five with the membrane, while the remaining two could not be unambiguously located [21].…”
Section: The New Genus Gammasphaerolipovirusmentioning
confidence: 79%
“…HRPV-1 and HHPV-1 are composed of a membrane vesicle containing two major structural proteins (48,49,53). Although HRPV-1 and HHPV-1 have different genome types (ssDNA versus dsDNA), their circular genomes share the same gene order, and they have homologous structural proteins (49,53).…”
mentioning
confidence: 99%
“…The nine (HRPV-1) and eight (HHPV-1) open reading frames (ORF) encode a putative replication initiation protein; two major structural proteins, VP3 and VP4 (VP for virion protein); and a postulated ATPase (HRPV-1 VP8) (49,53). Biochemical analyses of HRPV-1 have shown that VP4 is a spike protein anchored to the membrane and that VP3 is a membrane protein facing the particle interior where the genome resides, without associated nucleoproteins (48). The genome synteny of HRPV-1 and HHPV-1 (from the VP4-encoding gene to the ATPase-encoding gene) is also shared with the linear genome of the haloarchaeal virus His2, which was proposed previously to be spindle shaped (11,49,53).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It infects Halorubrum sp. and has a pleomorphic appearance with glycosylated spike structures protruding from its external membrane (49,50).…”
mentioning
confidence: 99%